Fundus findings in a series of patients with extrapulmonary tuberculosis in Thailand - Jirawison C. (2017)
© 2016 Published by the BMJ Publishing Group Limited. Aim The aim of this study was to determine the frequency of fundus abnormalities among patients who are undergoing or have recently completed treatment for extrapulmonary tuberculosis (eTB). Methods This is a prospective cross-sectional study conducted in a TB clinic of a tertiary hospital in northern Thailand. All patients who had eTB between January 2014 and August 2015 were invited by telephone to return to the clinic for fundus photography. Three uveitis specialists reviewed all photographs to identify posterior segment lesions that were consistent with ocular TB. Results A total of 265 patients were diagnosed with eTB during the specified period, of which 118 (44.5%) were reached by telephone and 60 (50.8%) participated in the study. A total of 7 eyes from six patients (10.0% of participants, 95% CI 2.2% to 17.8%) had lesions consistent with ocular TB. The group with possible ocular TB lesions was on average 16.8 years older than those without ocular lesions (p=0.01), but the two groups were otherwise not significantly different. Conclusion Ocular lesions consistent with TB were not rare in a group of patients who were undergoing or had recently completed treatment for eTB. Fundus examination may provide diagnostic information that could influence a clinician's beliefs when diagnosing eTB. Given the low costs and immediate results of eye examination, this diagnostic test should be considered in patients suspected for eTB, especially when other tests are negative.